Sociocriticismo: institucionalidad e historia de un cuerpo teórico en formación - Amoretti Hurtado, María (2003)
This artic1e offers a brief outline of the institutional vicissitudes and the epistemological controversies in the process of building the socio-critics as an historically defined academic option.